Energy‐efficient management using a traffic‐oriented routing scheme for cognitive radio networks. (8th June 2015) - Mavromoustakis, Constandinos X.; Mastorakis, George; Bourdena, Athina; Pallis, Evangelos
Summary: This paper elaborates on a traffic manipulation routing scheme that associates the moments of the traffic, targeting the maximization of the energy conservation, as well as the effective resource management of the network nodes. The energy conservation is achieved through the data flow coordination, in association with the data traffic volume and the resource exchange, between the nodes that exploit radio spectrum access in cognitive radio networking architectures. The routing scheme that is proposed in this paper interrelates the backward difference of traffic moments for each node based on a series model, together with the sleep‐time period, towards reflecting this measurement to the minimization of the nodes activity durations to achieve energy conservation. The effective operation of the routing scheme is achieved by exploiting a signalling mechanism that was adopted for the proper communication of the nodes over the available radio spectrum parts, such as the television white spaces. Simulation tests were conducted towards examining the validity of the proposed routing scheme via multiple performance evaluation experiments. Simulation results have shown the offered reliability and the efficiency of the proposed traffic‐aware scheme, in reference to the efficient energy consumption of the networking nodes and the minimization of the delays. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper proposes a traffic manipulation scheme incorporated into an energy‐efficient routing protocol that associates the moments of the traffic, targeting the maximization of the energy conservation and the effective resource management of network nodes. The energy conservation is achieved through the data flow coordination in association with the data traffic volume and the resource exchange, among secondary communicating nodes with heterogeneous spectrum availability in cognitive radio systems.